Restriction of essential amino acids dictates the systemic metabolic response to dietary protein dilution - Yap, Yann W.; Rusu, Patricia M.; Chan, Andrea Y.; Fam, Barbara C.; Jungmann, Andreas; Solon-Biet, Samantha M.; Barlow, Christopher K.; Creek, Darren J.; Huang, Cheng; Schittenhelm, Ralf Bernd; Morgan, Bruce; Schmoll, Dieter; et al. (Nature Communications, 2020)
Dietary protein dilution (DPD) promotes metabolic-remodelling and -health but the precise nutritional components driving this response remain elusive. Here, by mimicking amino acid (AA) supply from a casein-based diet, we demonstrate that restriction of dietary essential AA (EAA), but not non-EAA, drives the systemic metabolic response to total AA deprivation; independent from dietary carbohydrate supply. Furthermore, systemic deprivation of threonine and tryptophan, independent of total AA supply, are both adequate and necessary to confer the systemic metabolic response to both diet, and genetic AA-transport loss, driven AA restriction. Dietary threonine restriction (DTR) retards the development of obesity-associated metabolic dysfunction. Liver-derived fibroblast growth factor 21 is required for the metabolic remodelling with DTR. Strikingly, hepatocyte-selective establishment of threonine biosynthetic capacity reverses the systemic metabolic response to DTR. Taken together, our studies of mice demonstrate that the restriction of EAA are sufficient and necessary to confer the systemic metabolic effects of DPD.